Deoxycholic acid delays the wound healing of colonic epithelial cells via transmembrane G‐protein‐coupled receptor 5. Issue 1 (4th October 2021) - Azuma, Yuka; Uchiyama, Kazuhiko; Sugaya, Takeshi; Yasuda, Takeshi; Hashimoto, Hikaru; Kajiwara‐Kubota, Mariko; Sugino, Satoshi; Kitae, Hiroaki; Torii, Takashi; Mizushima, Katsura; Doi, Toshifumi; Inoue, Ken; et al.
Abstract: Background and Aim: Efficient intestinal wound healing is essential for good prognoses of ulcerative colitis (UC). Although bile acids and the transmembrane G‐protein‐coupled receptor (TGR) 5 have been reported to affect wound healing in intestinal epithelial cells, the detailed underlying mechanisms are unclear. Here, we investigated the role of TGR5 in wound healing in the context of colonic epithelial cells in the presence of bile acids. Methods: The expression of TGR5 in the colonic epithelium of both a dextran sulfate sodium (DSS)‐induced colitis mouse model (recovery phase), and UC patients in clinical remission, was evaluated. Young adult mouse colonic epithelial (YAMC) cells were then used to evaluate wound healing after treatment with deoxycholic acid (DCA); TGR5 was silenced in YAMC cells via shRNA‐transfection, and a wound‐healing assay in the presence of DCA was performed. Furthermore, we investigated the role of the activation of AKT in the context of wound healing. Results: The expression of TGR5 was decreased in the colonic epithelium of both mice with DSS‐induced colitis and UC patients. Additionally, DCA significantly delayed wound healing in YAMC cells but not in TGR5 silenced ones. Of note, the DCA‐induced activation of AKT signaling in YAMC cells was inhibited by TGR5 silencing, and AKT inhibitors prevented the wound healing delay induced by DCA. Conclusions: Overall, we show that DCA delays wound healing in the context of colonic epithelial cells through AKT activation. These results may support the development of new therapeutic approaches for epithelial regeneration in UC.